2018
DOI: 10.1111/bjep.12255
|View full text |Cite
|
Sign up to set email alerts
|

‘Putting oneself in someone else's shoes during childhood: How to learn it’ Training for preschool age children

Abstract: BackgroundPerspective taking, defined as the aptitude to understand the cognitive, affective, and visual point of view of others, represents a fundamental social ability for the development of socio‐cognitive and affective skills.AimsThe aim of the present study was to evaluate the possibility of promoting perspective taking in typically developmental preschoolers using an evidence‐based training procedure.Sample and MethodThe research used a pre‐test/post‐test quasi‐experimental design in which 206 typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
0
15
0
2
Order By: Relevance
“…Two of them are visual-perceptual tasks ( Flavell et al, 1981 ; Mori and Cigala, 2019 ): children were shown two tables featuring the same sketch/image on both sides, but with a different detail; the challenge was to consider both points of view. The third test is represented by a modified and adapted version of the “policeman task” ( Hughes and Donaldson, 1979 ; Mori and Cigala, 2019 ) consisting of a three-dimensional model in which the child’s task is to simulate the game of hide-and-seek, placing a character in such a way that the other character cannot see. The scene is presented so that the child’s point of view does not coincide with the characters’ point of view.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of them are visual-perceptual tasks ( Flavell et al, 1981 ; Mori and Cigala, 2019 ): children were shown two tables featuring the same sketch/image on both sides, but with a different detail; the challenge was to consider both points of view. The third test is represented by a modified and adapted version of the “policeman task” ( Hughes and Donaldson, 1979 ; Mori and Cigala, 2019 ) consisting of a three-dimensional model in which the child’s task is to simulate the game of hide-and-seek, placing a character in such a way that the other character cannot see. The scene is presented so that the child’s point of view does not coincide with the characters’ point of view.…”
Section: Methodsmentioning
confidence: 99%
“…Prosocial behavior and aggressiveness were investigated through direct non-participant observations by means of an observation grid, created on the basis of prosocial behaviors assessment code systems ( D’Odorico et al, 2000 ; Roche Olivar, 2002 ; Bergin et al, 2003 ; Cigala et al, 2015 ; Mori and Cigala, 2019 ). Observations were conducted in the kindergarten attended by children in three different 45-min sessions on different days during lunch and in moments of free play both before and after lunch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ennek részeként egy mesealapú fejlesztő programot dolgoztam ki, mivel korábbi kutatások (pl. Grazzani et al 2016;Mori & Cigala, 2018) igazolták, hogy a proszociális viselkedés különböző pszichikus elemeinek (pl. nézőpontváltás, érzelemmegértés) fejlesztése mesékkel is megvalósítható, így a módszert alkalmasnak tekintettem a segítő jellegű viselkedési formák fejlesztő kísérletéhez.…”
Section: A Kutatás Eredményeinekunclassified
“…A (1) kognitív nézőpontváltás esetén az egyén képes értelmezni a másik személy gondolatait, motivációját és szándékait (Baron-Cohen, 2001), a (2) vizuális nézőpontváltás a térbeli elhelyezkedés különböző nézőpontjainak értelmezését teszi lehetővé (Moll & Meltzoff, 2011), míg az (3) affektív nézőpontváltás segítségével az egyén a másik érzelmi állapotát tudja értelmezni, ami az empátia egyik legfőbb alapjának tekinthető (Hinnant & O'Brien, 2007). A nézőpontváltás és a proszociális viselkedés között szoros kapcsolat mutatható ki, minél jobb nézőpontváltó valaki, annál gondoskodóbb, segítőkészebb másokkal szemben (Cigala, Mori, & Fangareggi, 2015;Mori & Cigala, 2018). Empátiás törődés esetén arról kapunk információkat, hogy az egyén hogyan képes törődni mások problémáival (Davis, 1980;Gáspár & Kasik, 2015).…”
Section: éRzelmi Motiváció Empátia Szimpátiaunclassified